Pelatihan Pengolahan dan Pemanfaatan Minyak Jelantah Menjadi Sabun bagi Masyarakat Banjar Benai - Irfandi Irfandi; Dwi Putri Musdansi; Nofri Yuhelman; Nopriadi Nopriadi; Rosa Murwindra (Beru'-beru': Jurnal Pengabdian kepada Masyarakat, 2022)
Waste cooking oil is one of the wastes produced by the community. Waste cooking oil that is disposed of carelessly will cause environmental pollution and damage health. For this reason, used cooking oil needs to be processed into other ingredients that have benefits. This service aims to provide training on the use and processing of used cooking oil into soap for the village community of Banjar Benai. This training was carried out by way of material presentation and hands-on soap making training. Making soap from used cooking oil can be done by an inexpensive method and using easily obtained materials such as waste cooking oil, NaOH, dyes, fragrances, and water. Before being processed, the used cooking oil is filtered from the impurities. The cooking oil is then mixed with a solution of NaOH, enough fragrance and dye and stirred until soap is formed. The results of this activity are the level of community satisfaction with service activities is very good with 92.4% and an increase in public understanding about the use and processing of used cooking oil into soap for the people of Banjar Benai village.